Cardiac Rehabilitation in India: Results from the International Council of Cardiovascular Prevention and Rehabilitation's Global Audit of Cardiac Rehabilitation. Issue 1 (3rd April 2020) - Babu, Abraham Samuel; Turk-Adawi, Karam; Supervia, Marta; Jimenez, Francisco Lopez; Contractor, Aashish; Grace, Sherry L.
Background: Cardiac rehabilitation (CR) is recommended in clinical practice guidelines for comprehensive secondary prevention. While India has a high burden of cardiovascular diseases (CVD), availability and nature of services delivered there is unknown. In this study, we undertook secondary analysis of the Indian data from the global CR audit and survey, conducted by the International Council of Cardiovascular Prevention and Rehabilitation (ICCPR). Methods: In this cross-sectional study, an online survey was administered to CR programs, identified in India by CR champions and through snowball sampling. CR density was computed using Global Burden of Disease study ischemic heart disease (IHD) incidence estimates. Results: Twenty-three centres were identified, of which 18 (78.3%) responded, from 3 southern states. There was only one spot for every 360 IHD patients/year, with 3, 304, 474 more CR spaces needed each year. Most programs accepted guideline-indicated patients, and most of these patients paid out-of-pocket for services. Programs were delivered by a multidisciplinary team, including physicians, physiotherapists, among others. Programs were very comprehensive. Apart from exercise training, which was offered across all centers, some centers also offered yoga therapy. Top barriers to delivery were lack of patient referral and financial resources. Conclusions: Of all countries in ICCPR's global audit, the greatest need for CR exists in India, particularly in the North. Programs must be financially supported by government, and healthcare providers trained to deliver it to increase capacity. Where CR did exist, it was generally delivered in accordance with guideline recommendations. Tobacco cessation interventions should be universally offered.